Aquifer recharge and evapotranspiration from the rivers in western Kansas - Auvenshine, Sarah (Kansas State University, 2018)
Western Kansas has a semi-arid climate where the demand for water resources is greater than the natural supply. To meet the demand for irrigated agriculture, the groundwater has been extracted at a rate greater than the natural recharge rate, resulting in declining water table in the aquifer and reduced streamflow in the rivers and streams in the region. An assessment of the rivers in western Kansas was conducted to determine the fluxes between the river, groundwater, and the atmosphere. Riverbeds were instrumented to determine the conductivity of the riverbed sediments, the transmission losses of the Arkansas River were modeled to determine the interactions between the surface water and groundwater, and the evapotranspiration of the Arkansas River corridor was estimated using satellite remote sensing to quantify of water lost to the atmosphere. The Arkansas River and Cimarron River are shown to have a high hydraulic conductivity and a large infiltration capacity at the surface of the riverbed. However, the large surface infiltration capacity does not translate into large transmission losses, which are a fraction of the rate of the surface infiltration capacity of the riverbed. Thus, surface infiltration is only one factor of what controls the transmission losses. It is shown that transmission losses for a connected river-aquifer system are driven by induced infiltration by riparian vegetation. The interactions between the surface, groundwater and atmosphere were assessed over time, revealing that the flux to the atmosphere can be decoupled from the Arkansas River discharge and the groundwater recharge. While the declining discharge in the Arkansas River can be attributed to the extraction of groundwater resources and the management of surface water resource, the atmospheric fluxes are independent of the surface water and groundwater at an annual scale. When the river ecosystem is water stressed, the trees continue to draw water. This points to both the reliable store of water from the alluvial aquifer and the ability of the tree community to respond to water stress. While the water in the alluvial deposits are currently being lost from the system through evapotranspiration, this provides a potential store for consideration in future water management decisions.
Keywords: Evapotranspiration; Transmission losses; River; Groundwater recharge